Building Government Legitimacy: The Role of Public Trust, Transparency, and Social Media Effectiveness in the Dynamics of Public Perception - Budiana, Muhammad Budiana (PT Inovasi Pratama Internasional, 2025)
The development of governance in the digital era presents challenges and opportunities for building strong government legitimacy in the eyes of the public. This study aims to identify and analyze the relationship between public trust, government transparency, and social media effectiveness and government legitimacy through a literature review. This research is a descriptive qualitative study with a systematic literature review method conducted through a systematic search of academic publications in international databases such as Scopus, Web of Science, ScienceDirect, and Google Scholar. A purposive sampling technique was used to select articles with the inclusion criteria of English-language articles relevant to the research topic and published within the last ten years (2014-2024). This research is not limited to a particular geographical area but includes various developed and developing country contexts as the study population, thus enriching the analysis results. The results showed that public trust is the foundation of government legitimacy, which is strengthened by digital-based transparency and interactive communication through social media. These three variables are individually influential and form synergies in strengthening public legitimacy perceptions. This research emphasize the importance of integrating public trust, transparency, and social media effectiveness as sustainable modern governance strategies, especially in the context of digital transformation